Composite film material as well as preparation method and application thereof

By introducing a modified polyamide layer into the nanofiltration membrane, using positively charged materials and hydrolyzed materials, the existing nanofiltration membrane is solved in the low efficiency of lithium-magnesium separation, and efficient and low-cost magnesium ion separation is achieved, which is suitable for applications in the field of lithium-magnesium separation in salt lakes.

CN119701688APending Publication Date: 2025-03-28BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958606.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing commercial nanofiltration membranes are not efficient in lithium-magnesium separation, which consumes time, has high energy consumption and has environmental pollution problems.

Method used

A composite film material is used, which consists of a porous base film and a modified polyamide layer located in the surface and pores of the porous base film. The modified polyamide layer includes a polyamide base layer and a functional material grafted on its surface. The functional material includes a positively charged material and a positively charged material after hydrolysis, and the positively charged material has a nanosheet-like structure.

Benefits of technology

It improves the separation efficiency of magnesium ions, enhances the water permeability and magnesium selectivity of the membrane, reduces costs, is suitable for industrial production, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701688A_ABST
    Figure CN119701688A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of membrane separation, and particularly relates to a composite film material as well as a preparation method and application thereof. The invention provides a composite film material. The composite film material comprises a porous base film and modified polyamide layers located on the surface and in pores of the porous base film, the modified polyamide layer comprises a polyamide base layer and a functional material grafted on the surface of the polyamide base layer; the functional material comprises a positive charge material and a material with positive charges after hydrolysis. According to the invention, a functional material is introduced into a composite film material, so that the surface of the film can have strong positive electricity, separation of cations is facilitated, and meanwhile, a two-dimensional nano channel formed by assembling the positively charged material nanosheets greatly increases the water permeability and magnesium selectivity of the film; the problems of poor magnesium ion separation performance and poor water permeability in the magnesium ion-containing solution are solved. The composite film material provided by the invention is high in separation efficiency and low in cost, and has a wide application prospect in the field of salt lake lithium-magnesium separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a composite film material and a preparation method and application thereof. Background Art

[0002] Lithium is an important resource and has been widely used in secondary batteries, lubricants, nuclear industry, etc. Salt lakes are one of the important sources of lithium and usually contain a high magnesium-to-lithium ratio, which makes lithium-magnesium separation a key step in extracting lithium from salt lakes.

[0003] Traditional lithium-magnesium separation methods, such as solar evaporation, chemical precipitation, solvent extraction and electrodialysis, have many problems, such as long time consumption, high energy consumption and environmental pollution. In contrast, membrane separation has the advantages of high efficiency, energy saving and easy intensiveness, and has shown potential in lithium-magnesium separation. However, the existing commercial nanofiltration membranes cannot meet the requirements of efficient separation of lithium and magnesium. Summary of the invention

[0004] The object of the present invention is to provide a composite film material and a preparation method and application thereof. The composite film material provided by the present invention can more effectively promote the separation of magnesium ions.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a composite film material, comprising a porous base film and a modified polyamide layer located on the surface and in the pores of the porous base film;

[0007] The modified polyamide layer includes a polyamide base layer and a functional material grafted on the surface of the polyamide base layer;

[0008] The functional material comprises a positively charged material and a material that is positively charged after being hydrolyzed, and the positively charged material has a nano-sheet structure.

[0009] Preferably, the positively charged material comprises a layered double metal hydroxide;

[0010] The material with positive charge after hydrolysis includes polyethyleneimine and / or quaternary ammonium salt chitosan.

[0011] Preferably, the polyamide layer is obtained by interfacial polymerization of an amine compound and an acyl chloride compound;

[0012] The amine compound includes one or more of piperazine, m-phenylenediamine and p-phenylenediamine;

[0013] The acyl chloride compound includes one or more of trimesoyl chloride, isophthaloyl chloride and 5-isocyanatoisophthaloyl chloride.

[0014] Preferably, the thickness of the modified polyamide layer is 50-80 nm.

[0015] Preferably, the mass percentage of the positive material on the composite film material is 1 to 30%;

[0016] The mass percentage of the material with positive charge after hydrolysis on the composite film material is 1-50%.

[0017] The present invention also provides a method for preparing the composite film material described in the above technical solution, comprising the following steps:

[0018] sequentially coating a solution containing an amine compound and a solution containing an acyl chloride compound on the surface of the porous base film to perform an interfacial polymerization reaction to obtain a treated base film;

[0019] A solution containing functional materials is coated on the surface of the treated base film to carry out a grafting reaction to obtain the composite film material.

[0020] Preferably, the temperature of the interfacial polymerization reaction is room temperature, and the time is 10 to 60 seconds.

[0021] Preferably, the grafting reaction is carried out at room temperature and for 1 to 30 minutes.

[0022] The present invention also provides the use of the composite thin film material described in the above technical solution or the composite thin film material prepared by the preparation method described in the above technical solution as a nanofiltration membrane in magnesium ion separation.

[0023] Preferably, the magnesium ion separation includes lithium-magnesium separation or sodium-magnesium separation.

[0024] The present invention provides a composite film material, comprising a porous base film and a modified polyamide layer located on the surface and in the pores of the porous base film; the modified polyamide layer comprises a polyamide base layer and a functional material grafted on the surface of the polyamide base layer; the functional material comprises a positively charged material and a material with a positive charge after hydrolysis, and the positively charged material has a nanosheet structure. The present invention introduces functional materials into the composite film material, which can make the surface of the film have a strong positive charge, which is conducive to the separation of cations. At the same time, the two-dimensional nanochannels formed by the assembly of positively charged material nanosheets greatly increase the water permeability and magnesium selectivity of the membrane, solving the problems of poor magnesium ion separation performance and poor water permeability in magnesium ion-containing solutions. The composite film material provided by the present invention has high separation efficiency and low cost, and has broad application prospects in the field of lithium-magnesium separation in salt lakes.

[0025] The present invention also provides a method for preparing the composite thin film material described in the above technical solution, comprising the following steps: coating a solution containing an amine compound and a solution containing an acyl chloride compound on the surface of a porous base film in sequence, performing an interfacial polymerization reaction, and obtaining a treated base film; coating a solution containing a functional material on the surface of the treated base film, performing a grafting reaction, and obtaining the composite thin film material. The present invention sequentially introduces positively charged materials and materials with positive charges after hydrolysis into the thin film material through an interfacial polymerization method and an interfacial grafting method, and obtains a composite thin film material with a strong positive charge. The preparation method provided by the present invention is simple, has low energy demand, has a wide range of raw material sources, is low in cost, meets environmental protection requirements, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The MgAl(CO 3 )-SEM image of LDH colloidal dispersion;

[0027] Figure 2 This is a surface SEM image of the composite film material obtained in Example 1;

[0028] Figure 3 This is a cross-sectional SEM image of the composite film material obtained in Example 1;

[0029] Figure 4 This is the Zeta potential diagram of the composite thin film material obtained in Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a composite film material, comprising a porous base film and a modified polyamide layer located on the surface and in the pores of the porous base film;

[0031] The modified polyamide layer includes a polyamide base layer and a functional material grafted on the surface of the polyamide base layer;

[0032] The functional material comprises a positively charged material and a material that is positively charged after being hydrolyzed, and the positively charged material has a nano-sheet structure.

[0033] The composite film material provided by the present invention comprises a porous base film. In the present invention, the porous base film preferably comprises nylon, polysulfone, polyethersulfone or alumina porous ceramics.

[0034] The composite film material provided by the present invention comprises a modified polyamide layer located on the surface and in the pores of the porous base film; the modified polyamide layer comprises a polyamide base layer and a functional material grafted on the surface of the polyamide base layer. In the present invention, the polyamide layer is preferably obtained by interfacial polymerization of an amine compound and an acyl chloride compound; the amine compound preferably comprises one or more of piperazine (PIP), metaphenylenediamine (MPD) and paraphenylenediamine (PPD); the acyl chloride compound comprises one or more of trimesoyl chloride (TMC), isophthaloyl chloride (IPC) and 5-isocyanatoisophthaloyl chloride (ICIC). In the present invention, the molar ratio of the amine compound to the acyl chloride compound is preferably 6.5:1. In the present invention, the conditions of the interfacial polymerization reaction are described in the following preparation method and will not be repeated here. In the present invention, the thickness of the modified polyamide layer is preferably 50 to 80 nm, and more preferably 60 to 70 nm.

[0035] In the present invention, the positive material preferably comprises a layered double metal hydroxide; the double metal hydroxide preferably comprises MgAl(CO 3 )-LDH, ZnAl(CO 3 )-LDH、CoAl(CO 3 )-LDH and NiAl(CO 3 )-LDH; the material with positive charge after hydrolysis preferably includes polyethyleneimine and / or quaternary ammonium salt chitosan. In the present invention, the mass percentage of the positively charged material on the composite film material is preferably 1-30%, more preferably 1-20%; the mass percentage of the material with positive charge after hydrolysis on the composite film material is preferably 1-50%, more preferably 5-20%.

[0036] In the present invention, the MgAl(CO 3 )-LDH is preferably prepared by the method preferably comprising:

[0037] Under stirring conditions, a salt solution containing magnesium chloride and aluminum chloride is added to an alkaline solution to perform a coprecipitation reaction to obtain a reaction system; the alkaline solution includes sodium hydroxide and sodium carbonate.

[0038] After the reaction system is subjected to solid-liquid separation, the obtained precipitate is mixed with water and crystallized to obtain the MgAl(CO 3 )-LDH.

[0039] In the present invention, the concentration of magnesium chloride in the salt solution is preferably 0.4 mol / L, and the concentration of aluminum chloride is preferably 0.2 mol / L; the concentration of sodium hydroxide in the alkaline solution is preferably 0.3 mol / L, and the concentration of sodium carbonate is preferably 0.026 mol / L. In the present invention, the volume ratio of the salt solution to the alkaline solution is preferably 1:4. In the present invention, when the salt solution begins to drip into the alkaline solution, a coprecipitation reaction occurs; the time of the coprecipitation reaction is preferably 30 minutes.

[0040] In the present invention, the solid-liquid separation method is preferably centrifugal separation; after obtaining the precipitate, it is also preferred to wash the precipitate, and the centrifugal separation and washing are preferably repeated 2 to 3 times. In the present invention, the water is preferably deionized water; the crystallization temperature is preferably 100°C, and the time is preferably 16 hours; after the crystallization, it is also preferred to cool the obtained system to room temperature. In the present invention, the MgAl(CO 3 )-LDH is preferably present in the form of a colloidal dispersion, and the mass concentration of the colloidal dispersion is preferably 0.1-2%.

[0041] The present invention also provides a method for preparing the composite film material described in the above technical solution, comprising the following steps:

[0042] sequentially coating a solution containing an amine compound and a solution containing an acyl chloride compound on the surface of the porous base film to perform an interfacial polymerization reaction to obtain a treated base film;

[0043] A solution containing functional materials is coated on the surface of the treated base film to carry out a grafting reaction to obtain the composite film material.

[0044] The invention sequentially coats a solution containing an amine compound and a solution containing an acyl chloride compound on the surface of a porous base film, performs an interfacial polymerization reaction, and obtains a treated base film.

[0045] In the present invention, the mass concentration of the solution containing amine compounds is preferably 0.01-2%, more preferably 0.5-1%, the mass concentration of the solution containing acyl chloride compounds is preferably 0.01-1%, more preferably 0.025-0.5%, and the solvent of the solution containing acyl chloride compounds is preferably n-hexane. In the present invention, the ratio of the volume of the solution containing amine compounds to the radius of the porous base membrane is preferably 2mL:2cm.

[0046] In the present invention, the coating of the solution containing amine compounds is preferably carried out under vacuum conditions, and the vacuum degree of the vacuum conditions is preferably 0.01 to 1 bar, and more preferably 0.1 to 0.5 bar. In the present invention, coating under vacuum conditions can fully ensure that the solution containing amine compounds is fully impregnated into the interior of the porous base membrane.

[0047] In the present invention, the temperature of the interfacial polymerization reaction is preferably room temperature, the time is preferably 10 to 60 seconds, and more preferably 10 to 40 seconds. After the interfacial polymerization reaction is completed, the present invention also preferably includes drying, and the drying method is preferably drying with an air knife.

[0048] After obtaining the treated base film, the present invention coats a solution containing functional materials on the surface of the treated base film to carry out a grafting reaction to obtain the composite film material.

[0049] In the present invention, the mass concentration of the positively charged material in the solution containing the functional material is preferably 0.01 to 1%, more preferably 0.05 to 0.5%, and the mass concentration of the material with positive charge after hydrolysis is preferably 0.01 to 1%, more preferably 0.1 to 0.5%. In the present invention, the ratio of the volume of the solution containing the functional material to the radius of the porous base membrane is preferably 2 mL: 2 cm.

[0050] In the present invention, the temperature of the grafting reaction is preferably room temperature, and the time is preferably 1 to 30 minutes, and more preferably 1 to 10 minutes. In the present invention, during the grafting reaction, the functional material reacts with the unreacted acyl chloride groups on the treated base film to achieve the grafting of the functional material to the surface of the film. After the grafting reaction, the present invention also preferably performs water washing.

[0051] The present invention also provides the use of the composite thin film material described in the above technical solution or the composite thin film material prepared by the preparation method described in the above technical solution as a nanofiltration membrane in magnesium ion separation.

[0052] In the present invention, the magnesium ion separation preferably includes lithium-magnesium separation or sodium-magnesium separation.

[0053] In the present invention, the interception rate of the composite film material for magnesium chloride is preferably 95.31-96.02%, and the interception rate of lithium chloride is preferably 29.8-32.3%; the flux of the composite film material is preferably 21.68-38.03Lm -2 h - 1 bar -1 .

[0054] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0055] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Example 1

[0057] Under stirring conditions, a salt solution containing magnesium chloride and aluminum chloride (comprising 0.4 mol / L magnesium chloride concentration and 0.2 mol / L aluminum chloride, 50 mL) is simultaneously added to an alkaline solution (comprising 0.3 mol / L sodium hydroxide and 0.026 mol / L sodium carbonate, 200 mL), and a coprecipitation reaction is carried out for 30 min to obtain a reaction system;

[0058] The reaction system was centrifuged and washed twice at low speed, and the obtained precipitate was mixed with 200 mL of deionized water and placed in a reaction kettle, and kept at 100° C. for 16 h for crystallization to obtain MgAl(CO 3 )-LDH colloidal dispersion, mass concentration is 1%;

[0059] Under vacuum conditions of 0.1 bar, piperazine solution (PIP, 2 mL, mass concentration of 0.5%) was evenly dropped on the surface of a porous nylon base membrane (circle with a radius of 2 cm). When there was no excess PIP solution on the surface of the base membrane, trimesoyl chloride n-hexane solution (TMC, 2 mL, mass concentration of 0.025%) was added dropwise, reacted at room temperature for 20 seconds, and dried with an air knife to obtain a treated base membrane;

[0060] The surface of the treated base film was introduced with a solution containing functional materials (2 mL, containing polyethyleneimine with a mass concentration of 0.1% and LDH colloidal dispersion with a mass concentration of 0.05%), reacted at room temperature for 2 min, and then washed with deionized water to obtain a composite film material (wherein MgAl(CO 3 The mass percentage of )-LDH in the composite film material is 7.69%, and the mass percentage of polyethyleneimine in the composite film is 15.38%).

[0061] Example 2

[0062] MgAl(CO) was prepared in the same manner as in Example 1. 3 )-LDH colloidal dispersion;

[0063] Under vacuum conditions of 0.1 bar, piperazine solution (PIP, 2 mL, mass concentration of 0.5%) was evenly dropped on the surface of a porous nylon base membrane (circle with a radius of 2 cm). When there was no excess PIP solution on the surface of the base membrane, trimesoyl chloride n-hexane solution (TMC, 2 mL, mass concentration of 0.025%) was added dropwise, reacted at room temperature for 20 seconds, and dried with an air knife to obtain a treated base membrane;

[0064] The surface of the treated base film was introduced with a solution containing functional materials (2 mL, containing 0.2% polyethyleneimine by mass concentration and 0.1% LDH colloidal dispersion by mass concentration, containing 0.1 mol / L polyethyleneimine and 0.025 mol / L LDH colloidal dispersion), reacted at room temperature for 2 min, and then washed with deionized water to obtain a composite film material (wherein MgAl(CO 3 )-LDH content in the composite film material is 12.50% by weight, and polyethyleneimine content in the composite film is 25.00% by weight).

[0065] Example 3

[0066] MgAl(CO) was prepared in the same manner as in Example 1. 3 )-LDH colloidal dispersion;

[0067] Under vacuum conditions of 0.1 bar, piperazine solution (PIP, 2 mL, mass concentration of 1%) was evenly dropped on the surface of a porous nylon base membrane (circle with a radius of 2 cm). When there was no excess PIP solution on the surface of the base membrane, trimesoyl chloride n-hexane solution (TMC, 2 mL, mass concentration of 0.025%) was added dropwise, reacted at room temperature for 20 seconds, and dried with an air knife to obtain a treated base membrane;

[0068] The surface of the treated base film was introduced with a solution containing functional materials (2 mL, containing polyethyleneimine with a mass concentration of 0.1% and LDH colloidal dispersion with a mass concentration of 0.05%), reacted at room temperature for 2 min, and then washed with deionized water to obtain a composite film material (wherein MgAl(CO 3 The mass percentage of )-LDH in the composite film material is 4.35%, and the mass percentage of polyethyleneimine in the composite film is 8.69%).

[0069] Performance Testing

[0070] Test Example 1

[0071] Figure 1 The MgAl(CO 3 )-LDH colloidal dispersion SEM image; Figure 1It can be seen that it exhibits a regular lamellar structure with a lateral size range of about 100 nm.

[0072] Figure 2 This is the surface SEM image of the composite film material obtained in Example 1. Figure 3 This is a cross-sectional SEM image of the composite film material obtained in Example 1. Figures 2-3 It can be seen that the surface of the composite film material is dense and defect-free.

[0073] Figure 4 The Zeta potential diagram of the composite film material obtained in Example 1, the horizontal axis is the pH value, the vertical axis is the potential, the unit is mV, Figure 4 It can be seen that there is no isoelectric point, which means that the surface of the composite film material is positively charged at any pH.

[0074] Test Example 2

[0075] The composite thin film material obtained in Examples 1 to 3 was used as a nanofiltration membrane to perform a performance test;

[0076] (1) Permeation flux test

[0077] At 25°C, the effective filtration area of ​​the membrane was determined to be 3.14 cm using a lateral flow test apparatus. 2 .

[0078] Permeation flux is an important parameter used to describe the volume of permeate passing through a unit effective membrane area per unit time under specific pressure conditions. This parameter directly reflects the permeability of the nanofiltration membrane to the solution. The calculation formula for permeation flux (F) is as follows:

[0079]

[0080] Where: F represents the permeation flux of the membrane at a specified pressure, in Lm -2 h -1 bar -1 , V is the volume of the permeate, in L, A is the effective area of ​​the membrane, in m 2 , t represents the test time in h, and P represents the filtration pressure in bar.

[0081] After testing, the permeation flux of the nanofiltration membranes obtained in Examples 1 to 3 was 38.03 Lm -2 h -1 bar -1 、22.48Lm - 2 h -1 bar -1 and 21.68Lm -2 h-1 bar -1 .

[0082] (2) Testing the retention rate of nanofiltration membrane for magnesium and lithium

[0083] The retention rate (R) is an important indicator for evaluating the ability of nanofiltration membranes to intercept solutes during the filtration process. It represents the ratio of the solute concentration intercepted by the membrane to the solute concentration in the raw liquid. The retention rate is calculated as follows:

[0084]

[0085] Where: R represents the interception rate, the unit is percentage (%), C p It represents the concentration of solute in the permeate (i.e. the filtered liquid), C f Indicates the concentration of solute in the raw liquid (i.e., unfiltered liquid), and the unit is the same as C p The same; the test results are shown in Table 1;

[0086] Table 1 Rejection rate of lithium and magnesium of the composite film materials obtained in Examples 1 to 3

[0087]

[0088] It can be seen from Table 1 that the composite film material provided by the present invention has a 2+ It has a high retention capacity and can effectively achieve Mg 2+ separation.

[0089] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite film material, characterized in that: It comprises a porous base film and a modified polyamide layer located on the surface and in the pores of the porous base film; The modified polyamide layer includes a polyamide base layer and a functional material grafted on the surface of the polyamide base layer; The functional material comprises a positively charged material and a material that is positively charged after being hydrolyzed, and the positively charged material has a nano-sheet structure.

2. The composite film material according to claim 1, characterized in that: The positively charged material comprises a layered double metal hydroxide; The material with positive charge after hydrolysis includes polyethyleneimine and / or quaternary ammonium salt chitosan.

3. The composite film material according to claim 1, characterized in that: The polyamide layer is obtained by interfacial polymerization of an amine compound and an acyl chloride compound; The amine compound includes one or more of piperazine, m-phenylenediamine and p-phenylenediamine; The acyl chloride compound includes one or more of trimesoyl chloride, isophthaloyl chloride and 5-isocyanatoisophthaloyl chloride.

4. The composite film material according to claim 1, characterized in that: The thickness of the modified polyamide layer is 50-80 nm.

5. The composite film material according to claim 1, characterized in that: The mass percentage of the positive material on the composite film material is 1 to 30%; The mass percentage of the material with positive charge after hydrolysis on the composite film material is 1-50%.

6. The method for preparing the composite film material according to any one of claims 1 to 5, characterized in that: The following steps are involved: sequentially coating a solution containing an amine compound and a solution containing an acyl chloride compound on the surface of the porous base film to perform an interfacial polymerization reaction to obtain a treated base film; A solution containing functional materials is coated on the surface of the treated base film to carry out a grafting reaction to obtain the composite film material.

7. The preparation method according to claim 6, characterized in that: The temperature of the interfacial polymerization reaction is room temperature, and the time is 10 to 60 seconds.

8. The preparation method according to claim 6, characterized in that: The temperature of the grafting reaction is room temperature, and the time is 1 to 30 minutes.

9. Use of the composite film material according to any one of claims 1 to 5 or the composite film material prepared by the preparation method according to any one of claims 6 to 8 as a nanofiltration membrane in magnesium ion separation.

10. The use according to claim 9, characterized in that: The magnesium ion separation includes lithium-magnesium separation or sodium-magnesium separation.